Defining the phenotype of young healthy nucleus pulposus cells: Recommendations of the Spine Research Interest Group at the 2014 annual ORS meeting. Issue 3 (21st January 2015) - Risbud, Makarand V.; Schoepflin, Zachary R.; Mwale, Fackson; Kandel, Rita A.; Grad, Sibylle; Iatridis, James C.; Sakai, Daisuke; Hoyland, Judith A.
ABSTRACT Low back pain is a major physical and socioeconomic problem. Degeneration of the intervertebral disc and especially that of nucleus pulposus (NP) has been linked to low back pain. In spite of much research focusing on the NP, consensus among the research community is lacking in defining the NP cell phenotype. A consensus agreement will allow easier distinguishing of NP cells from annulus fibrosus (AF) cells and endplate chondrocytes, a better gauge of therapeutic success, and a better guidance of tissue‐engineering‐based regenerative strategies that attempt to replace lost NP tissue. Most importantly, a clear definition will further the understanding of physiology and function of NP cells, ultimately driving development of novel cell‐based therapeutic modalities. The Spine Research Interest Group at the 2014 Annual ORS Meeting in New Orleans convened with the task of compiling a working definition of the NP cell phenotype with hope that a consensus statement will propel disc research forward into the future. Based on evaluation of recent studies describing characteristic NP markers and their physiologic relevance, we make the recommendation of the following healthy NP phenotypic markers: stabilized expression of HIF‐1α, GLUT‐1, aggrecan/collagen II ratio >20, Shh, Brachyury, KRT18/19, CA12, and CD24. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:???–???, 2015.